Primary lateral sclerosis: consensus diagnostic criteria. Issue 4 (6th February 2020) - Turner, Martin R; Barohn, Richard J; Corcia, Philippe; Fink, John K; Harms, Matthew B; Kiernan, Matthew C; Ravits, John; Silani, Vincenzo; Simmons, Zachary; Statland, Jeffrey; van den Berg, Leonard H; ,; et al.
Abstract : Primary lateral sclerosis (PLS) is a neurodegenerative disorder of the adult motor system. Characterised by a slowly progressive upper motor neuron syndrome, the diagnosis is clinical, after exclusion of structural, neurodegenerative and metabolic mimics. Differentiation of PLS from upper motor neuron-predominant forms of amyotrophic lateral sclerosis remains a significant challenge in the early symptomatic phase of both disorders, with ongoing debate as to whether they form a clinical and histopathological continuum. Current diagnostic criteria for PLS may be a barrier to therapeutic development, requiring long delays between symptom onset and formal diagnosis. While new technologies sensitive to both upper and lower motor neuron involvement may ultimately resolve controversies in the diagnosis of PLS, we present updated consensus diagnostic criteria with the aim of reducing diagnostic delay, optimising therapeutic trial design and catalysing the development of disease-modifying therapy.